Effects of calcium supplementation on changes in the IL2, IL4, IL6, IL10 axes and oxidative stress in pregnant women at risk for pre-eclampsia - Erica de Brito Pitilin; Filomena Marafon; Beatriz da Silva Rosa Bonadiman; Bruno Bordin Pelazza; Micheli Mainardi Pillat; Jéssica Dotto de Lara; Patrícia Pereira de Oliveira; Margarete Dulce Bagatini; Janine Schirmer (BMC Pregnancy and Childbirth, 2024)
Abstract Background Pregnant women with hypertensive disorders are at increased risk for inflammatory diseases and oxidative stress. The dilemma raised by the best dosage of calcium supplementation on these factors is evident. The aim of the current study was to examine the effects of calcium on biomarkers of the purinergic system, inflammation and oxidative stress, which are factors contributing to vascular damage in pregnant women at high risk of pre-eclampsia. Methods A prospective, double-blind and placebo-controlled study conducted with 101 women at risk of pre-eclampsia were randomized to take 500 mg calcium/day or 1,500 mg calcium/day or placebo for 6 weeks from the 20th gestational week until delivery. Fasting blood samples were collected at the beginning of the study and 6 weeks after the intervention. Results Taking calcium supplements (500 mg calcium/day) led to a significant increase in ATP hydrolysis (p < 0.05), NTPDase activity with increased hydrolysis of ADP and AMP nucleotides in platelets and lymphocytes. In the intragroup analysis IL-2, IL-6, IL-4 and interferon-ɣ presented lower values in the calcium 1,500 mg/day group (p < 0.005). Oxidative stress was assessed by TBARS pro-oxidant marker, with an increase for the calcium groups when compared to the placebo group. The Vitamin C antioxidant marker presented a significant increase (p < 0.005) for the group that received high calcium doses. Conclusions Calcium administration for 6 weeks had antioxidant action and positively modulated the purinergic system and inflammatory markers in pregnant women at risk of pre-eclampsia.